Evaluasi Kegiatan Pelayanan Asuhan Kesehatan Gigi Dan Mulut Terhadap Pengetahuan Sikap Status Kesehatan Gigi Dan Mulut Siswa Sekolah Dasar - Dwi Suyatmi; Dwi Eni Purwati (POLTEKKES KEMENKES YOGYAKARTA, 2018)
Service Activities Dental and Oral Health Care is part of the School Dental Health Enterprises (UKGS) which aims to improve the knowledge, attitude and the ability to behave in the field of healthy living oral health. These activities include outreach, shared toothbrushes and dental examinations, but oral health care has no knowledge, so the researchers are interested to know the difference before and after the service activities of oral health care on knowledge, attitude, oral health status elementary students. The purpose of this research is to know the difference before and aftercare service activities against oral health knowledge, attitudes, and oral health status of elementary school students. This study used a quasi-experimental method with the design of One Group Pre-test - Post-test Design. The population in this study were elementary school students in the area of ??Gamping Sleman Yogyakarta with a sample of 179 students. Sampling techniques using saturation sampling. Results: Based on the analysis of different test (paired sample t-test) showed significant differences in knowledge, attitudes, oral hygiene, decay and Decay students between the before and after care service oral health (p<0.05). Conclusions: 1). Knowledge, attitude and degree of oral hygiene students after health care services increased oral better 2). There was a decrease in rate-test decay (teeth better ) and Decay (permanent teeth ) on the student after the service of oral health care.